Valuation of Go Stimuli or Devaluation of No-Go Stimuli? Evidence of an Increased Preference for Attended Go Stimuli Following a Go/No-Go Task - Inoue, Kazuya; Sato, Nobuya (Frontiers in Psychology, 2017)
Attentional inhibition that occurs during discrimination tasks leads to the negative evaluation of distractor stimuli. This phenomenon, known as the distractor devaluation effect also occurs when go/no-go tasks require response inhibition. However, it remains unclear whether there are interactions between attention and response controls when the distractor devaluation effect occurs. The aims of this study were to investigate whether attention to stimuli in the go/no-go task plays a facilitative role in distractor devaluation through response inhibition, and to clarify whether this effect reflects a decreased preference for no-go stimuli. Participants evaluated the preference for pictures before and after a go/no-go task. In Experiment 1 and 2, they made a go or no-go response depending on the category of pictures displayed (gummy candies or rice crackers), whereas in Experiment 3 they did on the basis digit category, even or odd numbers, superimposed on such pictures. Experiments 1 and 2 demonstrated that the pictures presented as no-go stimuli in the preceding go/no-go task were evaluated as less positive than the pictures presented as go stimuli. This devaluation effect reflected an increased preference for the go stimuli but not a decreased preference for the no-go stimuli. Experiment 3 indicated that response inhibition did not affect the preference for the pictures that had not received attention in a preceding go/no-go task. These results suggest that although attention plays an important role in differential ratings for go and no-go stimuli, such differences, in fact, reflect the valuation of go stimuli.